An investigation of pulse transit time as a blood pressure measurement method in patients undergoing carotid artery stenting. Issue 3 (June 2016) - Can, Yusuf; Kilic, Harun; Akdemir, Ramazan; Acar, Bilgehan; Edem, Efe; Kocyigit, Ibrahim; Vatan, Mehmet B.; Aksoy, Murat; Can, Nimet; Gunduz, Huseyin
Abstract : Introduction: Pulse transit time (PTT) is the duration that a pulse wave takes to travel between two different arterial points, and it may be useful in estimating blood pressure. The aim of this study was to investigate the PTT during carotid artery stenting, as well as its value in blood pressure estimation. Method: Thirty-four patients with critical carotid artery stenosis were enrolled in this study. The carotid PTT from the onset of the R-wave of electrocardiography to the pulse waveform at the carotid artery, obtained invasively during carotid artery catheterization, was measured. The carotid PTT was measured before and after stenting of the internal carotid artery. Results: The mean age was 70.4±8.0 years among the 34 patients enrolled (eight female patients, 21.9%). Measurements were obtained before and after carotid artery stenting. The heart rate (85.9±15.9 vs. 76.9±12.5 bpm, P <0.01), systolic blood pressure (162.8±28.6 vs. 126.0±31.7 mmHg, P <0.001), diastolic blood pressure (87.7±17.9 vs. 76.9±20.0 mmHg, P <0.01), and mean blood pressure (112.7±18.6 vs. 93.2±22.7 mmHg, P <0.001) were significantly decreased, whereas the carotid PTT (0.06±0.012 s vs. 0.07±0.012 s, P <0.001) was significantly increased after carotid stenting. The difference between the PTTs was negatively correlated with the systolic blood pressure ( r =−0.35, P =0.02) and diastolic blood pressure ( r =−0.4, P =0.01). Conclusion: After carotid stenting, the PTT increases significantly because of the lowering of the blood pressure. However, the relationship is not strong enough for the PTT to be used for blood pressure estimation.